2015
DOI: 10.15406/jdhodt.2015.03.00082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Functional Appliance Therapy on the Depth of the Pharyngeal Airways: Activator vs. Forsus

Abstract: The sample consisted of 25 adolescents (14 boys and 11 girls, average age 11 years 8 months), whose lateral cephalograms taken before (T 1 ) and after the treatment (T 2 ) with functional appliances (total 50) were collected. The lateral cephalometric radiographs were compiled from their clinical records kept at Research Article AbstractAims: The aim of this study was to evaluate the changes in Dento-skeletal components following orthopedic therapy of Class II skeletal malocclusions, and to assess the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
(32 reference statements)
1
3
0
3
Order By: Relevance
“…In this study, upper incisors did not show any changes in both groups. This was accordance with previous study 13 but against other studies, where investigators claim that upper incisors tip lingually by appliance. 11,15 Experimental group showed highly significant proclined and protruded lower incisors after treatment and decrease in overjet.…”
Section: Dentoalveolar Changessupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, upper incisors did not show any changes in both groups. This was accordance with previous study 13 but against other studies, where investigators claim that upper incisors tip lingually by appliance. 11,15 Experimental group showed highly significant proclined and protruded lower incisors after treatment and decrease in overjet.…”
Section: Dentoalveolar Changessupporting
confidence: 93%
“…[8][9][10][11][12][13] where as mandible was positioned anteriorly lead to decrease in maxilla-mandibular discrepancy. These observation were in accordance with the previous studied [9][10][11][12][13] where as these changes were insignificant on comparison with control group indicating that PowerScope TM Class II Corrector appliance has no effects on both maxilla and mandible.This finding is in accordance with previous study 8 Vertical facial height showed statistically insignificant. This result was in agreement with other previous studies.…”
Section: Skeletal Changesmentioning
confidence: 99%
“…Se observó una diferencia en la longitud mandibular de 1,53 mm en pacientes tratados con AF removibles en comparación con el grupo no tratado (16) .Se ha reportado que el AF Sander Bite Jumping produce un mayor aumento de la longitud mandibular (3,40 mm), seguido en orden decreciente por Twin Block, Bionator, Harvold Activator y Fränkel (16) . Sin embargo, otros autores no han mostrado cambios en el crecimiento mandibular (17,18) . De la misma manera, no hay consenso sobre los efectos de los AF en el crecimiento mandibular (16,18) También hay diferentes maneras de medir los cambios en el crecimiento mandibular (16) .…”
Section: Discussionunclassified
“…Existen reportes que comparan resultados usando AF fijos y AF removibles. Así, Taki y Ghaffarpasand (17) no encontraron cambios significativos en cuanto a crecimiento o posición maxilar para ambos grupos (AF fijos y removibles). También observaron que la posición mandibular avanzó significativa y favorablemente en ambos grupos.…”
Section: Discussionunclassified
See 1 more Smart Citation